Analysis of the Longevity Assumptions of Employers' Occupational Pension Schemes - Wu, Jian (2007)
Occupational pension schemes have experienced important challenges in recent years. There is obvious increase in the expectation of life (longevity risk), and therefore an increase in the cost of the pension. Defined Benefit Pension Scheme has great impact on the cost of employers. This makes many companies in UK and other countries have large deficit. Employers now have to concern about pension schemes in their reported accounts. IAS 19 requires firms to understand their assets and liabilities of their pension schemes. Before 2005, there were not many companies disclose mortality assumptions. However, from 2006, most FTSE 100 firms have done so.